Landscape of Physical Activity and Quality of Life Research in Breast Cancer Survivors: Topic Modeling Analysis - Ryu, Suryeon; An, Ki-Yong; Song, Min; Gao, Zan (Journal of clinical medicine, 2025)
Background/Objectives: Physical activity (PA) is widely recognized as a beneficial approach to improving the health-related quality of life (HRQoL) of breast cancer survivors. This study explored key research topics and emerging trends in studies related to PA and HRQoL among breast cancer survivors. Methods: Titles and abstracts of 3847 English-language research articles (2000–2024) were retrieved from PubMed, EMBASE, Web of Science, and Scopus using keywords related to ‘breast cancer’, ‘PA/exercise’, and ‘HRQoL’. A text-mining algorithm based on the Dirichlet-multinomial regression approach in Python was applied to identify the top 10 research topics and their trends over time. Results: In total, 10 key topics emerged: (1) Quality of Life and Well-being, (2) Cancer Treatment and Health-Related Fitness, (3) Supportive Care and Psychosocial Factors, (4) Survivorship, Palliative Care, and Integrative Medicine, (5) Physical Activity and Sedentary Behaviors, (6) Upper Limb-Related Side Effects, (7) Cancer-Related Fatigue and Symptoms, (8) Epidemiological and Clinical Factors, (9) Side Effects of Cancer Treatment, and (10) Weight Management. Among these, Topics 1, 2, 3, 8, and 9 followed upward trajectories, while others showed relatively stable trends. Conclusions: Findings highlight that PA research on breast cancer survivors’ HRQoL spans all stages of survivorship and considers both clinical outcomes and psychosocial and emotional well-being. Understanding how PA and HRQoL have been represented in research helps clarify which survivor needs have received attention and which remain underexplored. These thematic patterns underscore growing acknowledgement of survivors’ lived experiences and offer a roadmap for addressing future research and care gaps.